Conociendo a los personajes de mi comunidad - Trujillo Eguizábal, Kelly Soledad (2018)
The work of professional proficiency entitled "Knowing the characters of the community" is within the area of social personnel, whose assigned competence was: the development of relations of democratic coexistence, with its capacity recognizes the elements and characters characteristic of their community and interacts with them in different activities, visits and meetings, and their indicator was identified to the characters of their community; which was based on theoretical foundations on issues of democratic coexistence, conflict management, social environment and community. And it is the responsibility of adults (parents and teachers) to train people capable of respecting, accepting, tolerating themselves, knowing how to put into practice democratic values; also make children know and value their culture, their customs, and seek the common good, but also know and respect the personalities, authorities of their community and recognize the role they fulfill. Which was materialized through pedagogical practice, based on a learning session, which on this occasion became a fundamental tool to foster consensus agreements among the members of a community, in order to regulate the coexistence in school and ensure for the welfare of all students, it is also based on constructivist pedagogical theories.